Answer:
The expression
=
Explanation:
Given
Required
Products of both
To do this, we have to apply the laws of indices,
Follow the highlighted steps
Step 1: Multiply both parameters directly
Since they both have the same roots, they can be multiplied directly according to the law of indices
becomes
Step 2: Apply the 1st law of indices
First law of indices states that
So,
becomes
=
=
=
=
Step 3: Rewrite the expression
=
Step 4: Expand the Expression in bracket
=
Break down into bits
=
=
=
=
=
=
=
=
=
Hence, the expression
=